Pengaruh Citra Merek Dan Harga Terhadap Minat Beli Ulang Yang Dimediasi Oleh Kepuasan Pelanggan Sunscreen Nivea Di Kota Bandung - Della Yoanda; Tania Adialita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The study aims to analyze the influence of brand image and price on repurchase intention mediated by customer satisfaction for Nivea sunscreen customers in Bandung. Methods of quantitative approach using surveys based on deductive reasoning. Nivea female sunscreen users who are resident in Bandung city, especially those who are in a productive age, that is, 17 years of age, are the population in this study. The convenience sampling technique is used to collect samples of as many as 120 people for this study. The data used comes from online surveys using cross-sectional data collection techniques or shot studies. The results of the research showed that brand image and price had a positive and significant influence on repurchase intention. Then, customer satisfaction plays a role in mediating the influence of brand image and price on repurchase intention. Based on the results, it is known that interest in resale is directly or indirectly influenced by brand image and price, this can be a serious concern for managers to be able to improve the brand image and price so that it can increase the interest of resale or repurchase intention for the Nivea sunscreen. Keywords : Brand Image, Price, Customer Satisfaction, Repurchase Intention